2020
DOI: 10.1093/europace/euaa226
|View full text |Cite
|
Sign up to set email alerts
|

Novel electroanatomical map for permanent his bundle pacing: the Mont Blanc approach - influence of the learning curve and procedural outcome

Abstract: Aims Pacing the specific conduction system like the Bundle of His (HB) can lead to more physiologic activation patterns compared to traditional right ventricular apical pacing. The aim of this study was to estimate the feasibility and value of electroanatomical mapping (EAM) for HB pacing during the learning curve and its impact on procedural outcome. Methods and results Fifteen consecutive patients were treated using EAM of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
15
1
1
Order By: Relevance
“…The potential benefit (e.g. minimizing procedure and fluoroscopy times) during the learning curve was confirmed by Imnadze et al using His voltage mapping to guide lead positioning 11 . In addition, EAM allows for better visualization and an understanding of the individual anatomy that may be crucial in challenging cases e.g.…”
Section: Discussionmentioning
confidence: 93%
“…The potential benefit (e.g. minimizing procedure and fluoroscopy times) during the learning curve was confirmed by Imnadze et al using His voltage mapping to guide lead positioning 11 . In addition, EAM allows for better visualization and an understanding of the individual anatomy that may be crucial in challenging cases e.g.…”
Section: Discussionmentioning
confidence: 93%
“…In published experiences of His bundle pacing with the guidance of a mapping system, the use of fluoroscopy was dramatically reduced but not completely eliminated (with very few exceptions 14 ), as minimal fluoroscopy was used in some phases of the procedure as the vein puncture, the lead screwing, the delivery catheter slitting, the implantation of others leads, and to adjust the tension and the final position of the implanted leads. [9][10][11][12][13] In LBBAP, the mapping system allows to precisely choose the site of lead implantation, by measuring the distance of the initial lead screwing point from the His bundle potential recording J o u r n a l P r e -p r o o f 7 sites and also the depth of lead advancement from that point, inside the interventricular septum.…”
Section: Discussionmentioning
confidence: 99%
“…Case series and observational and case-control studies, 9 , 10 , 11 , 12 , 13 mainly regarding His bundle pacing, have shown that this approach allows to minimize procedure and fluoroscopy times compared to the conventional fluoroscopy-guided approach. In published experiences of His bundle pacing with the guidance of a mapping system, the use of fluoroscopy was dramatically reduced but not completely eliminated (with very few exceptions 14 ), as minimal fluoroscopy was used in some phases of the procedure, such as the vein puncture, the lead screwing, the delivery catheter slitting, the implantation of others leads, and the adjustment of the tension and the final position of the implanted leads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently a study was published for selecting optimal His pacing site using EAM in 15 patients, employing EAM mapping and implant at the largest His amplitude signal. 24…”
Section: Previous Studies With Eam-guided Lead Implantationmentioning
confidence: 99%